Answer

Verified

486.3k+ views

Hint: Factorization of a quadratic equation gives us roots. Here the roots are given. We can follow the reverse process to find the required quadratic equation and then compare it with the given equation to get coefficients a, b.

Complete step-by-step answer:

The given quadratic equation is $a{x^2} + 7x + b = 0$

The roots of this equation are given as $x = \dfrac{2}{3}\;\& \;x = - 3$.

Then we can write as

$\left( {x - \dfrac{2}{3}} \right)\left( {x - ( - 3)} \right) = 0$ It will be the quadratic equation found from the given roots.

$ \Rightarrow \left( {x - \dfrac{2}{3}} \right)\left( {x + 3} \right) = 0$

On simplification of the above equation,

$ \Rightarrow {x^2} + 3x - \dfrac{{2x}}{3} - \dfrac{{2 \times 3}}{3} = 0$

$ \Rightarrow {x^2} + \dfrac{7}{3}x - 2 = 0$

Multiplying the above equation with 3 on both sides, we get

$ \Rightarrow 3{x^2} + 7x - 6 = 0$

Comparing the above equation with the given quadratic equation $a{x^2} + 7x + b = 0,$ we get

a = 3, b = –6.

$ \Rightarrow {a^2} + {b^2} = {(3)^2} + {( - 6)^2} = 9 + 36 = 45$

$\therefore $ The value of ${a^2} + {b^2} = 45$

Note: We can use a different way to solve the given problem using sum of the roots and product of the roots. Standard form of a quadratic equation with roots a, b can be written as

${x^2} - (sum\;of\;roots)x + product\;of\;roots = 0$

${x^2} - (a + b)x + ab = 0$

Complete step-by-step answer:

The given quadratic equation is $a{x^2} + 7x + b = 0$

The roots of this equation are given as $x = \dfrac{2}{3}\;\& \;x = - 3$.

Then we can write as

$\left( {x - \dfrac{2}{3}} \right)\left( {x - ( - 3)} \right) = 0$ It will be the quadratic equation found from the given roots.

$ \Rightarrow \left( {x - \dfrac{2}{3}} \right)\left( {x + 3} \right) = 0$

On simplification of the above equation,

$ \Rightarrow {x^2} + 3x - \dfrac{{2x}}{3} - \dfrac{{2 \times 3}}{3} = 0$

$ \Rightarrow {x^2} + \dfrac{7}{3}x - 2 = 0$

Multiplying the above equation with 3 on both sides, we get

$ \Rightarrow 3{x^2} + 7x - 6 = 0$

Comparing the above equation with the given quadratic equation $a{x^2} + 7x + b = 0,$ we get

a = 3, b = –6.

$ \Rightarrow {a^2} + {b^2} = {(3)^2} + {( - 6)^2} = 9 + 36 = 45$

$\therefore $ The value of ${a^2} + {b^2} = 45$

Note: We can use a different way to solve the given problem using sum of the roots and product of the roots. Standard form of a quadratic equation with roots a, b can be written as

${x^2} - (sum\;of\;roots)x + product\;of\;roots = 0$

${x^2} - (a + b)x + ab = 0$

Recently Updated Pages

Who among the following was the religious guru of class 7 social science CBSE

what is the correct chronological order of the following class 10 social science CBSE

Which of the following was not the actual cause for class 10 social science CBSE

Which of the following statements is not correct A class 10 social science CBSE

Which of the following leaders was not present in the class 10 social science CBSE

Garampani Sanctuary is located at A Diphu Assam B Gangtok class 10 social science CBSE

Trending doubts

Derive an expression for drift velocity of free electrons class 12 physics CBSE

Which are the Top 10 Largest Countries of the World?

Write down 5 differences between Ntype and Ptype s class 11 physics CBSE

The energy of a charged conductor is given by the expression class 12 physics CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Derive an expression for electric field intensity due class 12 physics CBSE

How do you graph the function fx 4x class 9 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Derive an expression for electric potential at point class 12 physics CBSE